Pyrolisis System terhadap Sampah Plastik Polyprophylene (PP) Menjadi Bahan Bakar - Wahyu Arini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
Abstract: The purpose of this study was to degrade Polypropylene plastic waste into fuel using a pyrolysis system. The method used to analyze the data from the pyrolysis process in this study is an experimental method, while the analysis used is quantitative data analysis, using existing calculations to analyze polypropylene plastic pyrolysis oil. Data collection techniques through three pyrolysis processes, namely 1 hour, 2 hours, and 3 hours. The results of the study through 3 pyrolysis processes at different times obtained that PP plastic waste produced oil, namely 778 ml at 1 hour, 926 ml at 2 hours and 1145 ml at 3 hours. The density value of the pyrolysis oil was weighed after testing. The calorific value in this study ranged from 0.75 to 0.78 Kg/L with the lowest specific gravity in sample 1 and the highest in sample 3. Data on the efficiency of oil produced by waste PP plastic through 3 experiments in the pyrolysis process showed that PP plastic waste was quite good in its efficiency level in producing oil, namely 52%; 62%; 76%. In conclusion, the efficiency of PP plastic waste into fuel is also influenced by various factors such as the pyrolysis equipment used, reactor temperature, conversion time, and others. So that through this research it was found that polypropylene (PP) plastic waste can be converted into fuel using the pyrolysis method with two types of condenser pyrolysis equipment. Keywords: Fuel, Polypropylene, Pyrolysis